2014
DOI: 10.1037/cep0000013
|View full text |Cite
|
Sign up to set email alerts
|

Language proficiency and metacognition as predictors of spontaneous rehearsal in children.

Abstract: Despite decades of research on fundamental memory strategies such as verbal rehearsal, the potential underlying skills associated with the emergence of rehearsal are still not fully understood. Two studies examined the relative roles of language proficiency and metamemory in predicting rehearsal use, as well as the prediction of metamemory performance by language proficiency. In Study 1, 59 children, 5 to 8 years old, were administered a serial recall task, 2 language measures, a nonverbal cognitive measure, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 70 publications
5
20
0
Order By: Relevance
“…Additionally, given the links between metamemory and language, we sought to examine the role that language proficiency plays for those with ASDs. In an earlier study examining the relationship among language proficiency, metamemory function and strategy use in TD children, we found that language proficiency was a strong predictor of strategy use, and also accounted for the relationship between metamemory and strategy use (Bebko et al, 2014). We expect that children with ASDs will display a similar pattern of results when language proficiency and metamemory knowledge are used as predictors of rehearsal and memory performance.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Additionally, given the links between metamemory and language, we sought to examine the role that language proficiency plays for those with ASDs. In an earlier study examining the relationship among language proficiency, metamemory function and strategy use in TD children, we found that language proficiency was a strong predictor of strategy use, and also accounted for the relationship between metamemory and strategy use (Bebko et al, 2014). We expect that children with ASDs will display a similar pattern of results when language proficiency and metamemory knowledge are used as predictors of rehearsal and memory performance.…”
Section: Introductionmentioning
confidence: 95%
“…Since a delay or lack of language acquisition is a common feature in ASD (indeed, it is often the first recognized symptom; Lord and Luyster, 2009), it is not surprising that the acquisition of language-based memory strategies would correspondingly be delayed. Bebko et al (2014) proposed a model in which they argued more generally that chronological age should be regarded as more of a summary descriptor variable than a predictor. That is, age is simply a stand-in that marks the typical development of underlying skills, such as language proficiency and metamemory, and it is these skills that are more specifically related to the development of rehearsal strategies and the subsequent benefits to recall performance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations